Remediation of Ex-Unlicensed Gold Mining Using Rice Husk Biochar: its Effect on Reducing Mercury Levels - Riza Hamkary Salam; Taufik Fauzi; A. A. Ketut Sudharmawan; Mulyati; Suwardji (Jurnal Biologi Tropis, 2023)
: The dangers of mercury in nature cause negative impacts on the environment and humans. The nature of mercury is bioaccumulative and toxic, and it cannot be degraded quickly but only through valence transformation. One effort that can be made to reduce the level of toxicity from mercury is to use biochar as an adsorbent agent in the soil. This article's goal is to review data regarding the use of biological charcoal (biochar) as a soil adsorbent for mercury. In order to clean up soil that has been contaminated with mercury (Hg), rice husk biochar plays a crucial function. Other than that, by using these organic materials instead of synthetic ones, soil production can be increased while environmental impact is reduced by 56%. Mercury is absorbed by biochar through a number of different mechanisms, including: (1) electrostatic bonds; (2) K+ and Na+ with Hg2+ and Hg+ ions simultaneously; (3) covalent reduction of mercury from Hg2+ to Hg+ and Hg0; (4) formation of a mineral complex (Hg2(OH)2) through precipitation of Hg2+ with carboxyl groups, such as lactones; and (5) complexation reactions on oxygen-containing functional groups such as - In comparison to soil alone, the use of biochar along with other organic elements can boost the capacity of heavy metal adsorption. With this combination, mercury levels were reduced to 12.45 ppm while soil pH increased dramatically from 0.3 to 1.33 units, near to neutral.